Bahasa Inggris - Mohammad Rifqi Alfarizi; Lalu Muhamad Jaelani (Institut Teknologi Sepuluh Nopember, 2026)
Urban air quality monitoring requires methods that are both comprehensive and cost-effective. Sentinel-5P TROPOMI satellite data are freely available; however, their units (mol/m²) cannot directly represent surface pollutant concentrations (μg/m³) without the Vertical Column Height (VCH) parameter, which is commonly assumed to be constant. This assumption contradicts the dynamic nature of the atmosphere. This study demonstrates that VCH is inherently dynamic through the integration of Sentinel-5P data with in-situ air quality sensor observations in Surabaya City. Daily VCH values were calculated for SO₂, CO, and NO₂ at the Kebonsari and Wonorejo monitoring stations throughout 2024 by pairing Vertical Column Density (VCD) data (retrieved via Google Earth Engine) with surface pollutant concentrations (obtained from the Surabaya Environmental Agency) based on matching dates and coordinates. The results show that VCH varies significantly on both daily and monthly scales, indicating that a static VCH assumption is not representative. The correlation between VCH and in-situ concentrations is negative, with the following order of strength: CO (r = −0.7989; R² = 0.6383) > NO₂ (r = −0.5913; R² = 0.3496) > SO₂ (r = −0.3818; R² = 0.1457), consistent with the atmospheric lifetime of each pollutant. Additional analysis shows that MODIS surface temperature shows weak positive correlations with VCH for all pollutants: SO₂ (r = 0.2903; R² = 0.0843) > CO (r = 0.2464; R² = 0.0607) > NO₂ (r = 0.0033; R² ≈ 0.0000), indicating that surface temperature alone is insufficient to explain vertical pollutant distribution. A dynamic VCH approach is therefore necessary for more accurate satellite-to-surface pollutant conversion, and future models require integration of more comprehensive meteorological parameters